Cleaning up the 'Bigmessidae': Molecular phylogeny of scleractinian corals from Faviidae, Merulinidae, Pectiniidae and Trachyphylliidae - Baird Andrew H; Licuanan Wilfredo Y; Huang Danwei; Fukami Hironobu (BMC Evolutionary Biology, 2011)
Abstract Background Molecular phylogenetic studies on scleractinian corals have shown that most taxa are not reflective of their evolutionary histories. Based principally on gross morphology, traditional taxonomy suffers from the lack of well-defined and homologous characters that can sufficiently describe scleractinian diversity. One of the most challenging clades recovered by recent analyses is 'Bigmessidae', an informal grouping that comprises four conventional coral families, Faviidae, Merulinidae, Pectiniidae and Trachyphylliidae, interspersed among one another with no apparent systematic pattern. There is an urgent need for taxonomic revisions in this clade, but it is vital to first establish phylogenetic relationships within the group. In this study, we reconstruct the evolutionary history of 'Bigmessidae' based on five DNA sequence markers gathered from 76 of the 132 currently recognized species collected from five reef regions in the central Indo-Pacific and the Atlantic. Results We present a robust molecular phylogeny of 'Bigmessidae' based on the combined five-gene data, achieving a higher degree of resolution compared to previous analyses. Two Pacific species presumed to be in 'Bigmessidae' are more closely related to outgroup clades, suggesting that other unsampled taxa have unforeseen affinities. As expected, nested within 'Bigmessidae' are four conventional families as listed above, and relationships among them generally corroborate previous molecular analyses. Our more resolved phylogeny supports a close association of Hydnophora (Merulinidae) with Favites + Montastraea (Faviidae), rather than with the rest of Merulinidae, i.e., Merulina and Scapophyllia. Montastraea annularis, the only Atlantic 'Bigmessidae' is sister to Cyphastrea, a grouping that can be reconciled by their septothecal walls, a microstructural feature of the skeleton determined by recent morphological work. Characters at the subcorallite scale appear to be appropriate synapomorphies for other subclades, which cannot be explained using macromorphology. Indeed, wide geographic sampling here has revealed more instances of possible cryptic taxa confused by evolutionary convergence of gross coral morphology. Conclusions Numerous examples of cryptic taxa determined in this study support the assertion that diversity estimates of scleractinian corals are erroneous. Fortunately, the recovery of most 'Bigmessidae' genera with only minor degrees of paraphyly offers some hope for impending taxonomic amendments. Subclades are well defined and supported by subcorallite morphological features, providing a robust framework for further systematic work.